The Trajectory of Brazilian Immunization Program between 1980 and 2018: From the Virtuous Cycle to the Vaccine Coverage Decline - Marcia Michie Minakawa; Paulo Frazão (Vaccines, 2023)
Background: Public health policies are crossed by economic and political interests that can affect the maintenance of the immunization programs and their vaccination coverages. The aim was to investigate the political and economic conditions that marked the trajectory of the Brazilian immunization program from 1980 to 2018. Methods: Documentary research gathered data on public expenditures with epidemiological surveillance and vaccine procurement and nationwide estimates of vaccine coverage. The scientific literature on the program’s implementation and the country’s political and economic conditions was examined. The theoretical approach was based on historical institutionalism. Results: The results showed rising, high rates maintaining and falling vaccination coverages in the period. As of 2010, there was a tendency for a reduction in total federal spending on epidemiological surveillance, putting pressure on the budgets of the sub-national governments in their respective areas of coverage, and on federal spending in dollars for the acquisition of immunobiologicals and inputs. Conclusions: The amplitude and complexity of the program’s trajectory have been crossed by diverse dynamics conditioned by economic and political interests reflecting at a deeper level the advance of capitalism through fiscal austerity measures over democracy’s aspirations for greater balance and justice in the distribution of resources.